Rare Presentation of Giant Cell Tumor in the Internal Auditory Canal: Case Report and Review of the Literature - Jada, Ajit S.; Shrivastava, Raj K.; Mannan, Abul; Kobets, Andrew; Manolidis, Spiros (Journal of Neurological Surgery Reports, 2015)
Giant cell tumor (GCT) is a benign but locally aggressive bone tumor that usually involves the end of long bones. It is a relatively common neoplasm in patients, constituting 5 to 10% of all benign bone tumors. Approximately 2% of GCTs occur in the craniofacial skeleton with a predilection for the ethmoid, sphenoid, and temporal bones. The skull base location is unique and not commonly described. Hearing loss, headache, tinnitus, and subcutaneous masses are the most commonly reported symptoms in GCTs of the skull base. In this case report we present the first description of a GCT within the internal auditory canal causing cranial neuropathy and review the recent pertinent literature.
Keywords: giant cell tumor; internal auditory canal; skull base tumor